«No one’s territory»: State and human development in Madre de Dios - Fuentes, Alejandra (2018)
Traditionally, one of the most important questions in social sciences has been one that asks about differences in levels of development (between regions, countries and sub-national units). However, it is only in the last decades that development has begun to be understood from a perspective centered on people and, particularly, on their well-being and freedom to live the life they choose to live. This article argues why a region like Madre de Dios—characterized by its geographical complexity, illegal economies, high rates of human trafficking and other problems—has managed to maintain relatively successful levels in the Development Index over time. Human. From a sub-national perspective, it is proposed that in this region three different levels of human development coexist in three different areas of the territory that are overshadowed by regional measurement. These three differentiated levels, in turn, are the result of different patterns of relations between State and society based on two conditions: (1) the type of non-state actors and (2) the nature of the interaction.